Decoupled richness of generalist anaerobes and sulphate‐reducing bacteria is driven by pH across land uses in temperate soils. (18th September 2020) - George, Paul B. L.; Coelho, Katia P.; Creer, Simon; Lebron, Inma; Robinson, David A.; Jones, Davey L.
Abstract: Sulphate‐reducing bacteria (SRB) represent a key biological component of the global sulphur (S) cycle and are common in soils, where they reduce SO4 2− to H2 S during the anaerobic degradation of soil organic matter. The factors that regulate their distribution in soil, however, remain poorly understood. We sought to determine the ecological patterns of SRB richness within a nationwide 16S metabarcoding dataset. Across 436 sites belonging to seven contrasting temperate land uses (e.g., arable, grasslands, woodlands, heathland and bog), SRB richness was relatively low across land uses but greatest in grasslands and lowest in woodlands and peat‐rich soils. There was a shift in dominant SRB taxa from Desulfosporosinus and Desulfobulbus in arable and grassland land uses to Desulfobacca in heathland and bog sites. In contrast, richness of other generalist anaerobic bacterial taxa found in our dataset (e.g., Clostridium, Geobacter and Pelobacter ) followed a known trend of declining richness linked to land‐use productivity. Overall, the richness of SRBs and anaerobes had strong positive correlations with pH and sulphate concentration and strong negative relationships with elevation, soil organic matter, total carbon and carbon‐to‐nitrogen ratio. It is likely that these results reflect the driving influence of pH and competition for optimal electron acceptors with generalist anaerobic bacteria on SRB richness. Highlights: Sulphate‐reducing bacteria (SRB) are key but rare soil biota that may compete with other anaerobes As UK sulphur deposition rates fall, local populations of SRB may also decline in soils Sulphate concentrations were higher in arable and wooded sites, not at higher elevation as expected SRB richness was lower than generalist anaerobes, with peaks in grasslands and a drop in lowland woods.